The Impact Of Worker Experience And Health Level To Vibration Absorbed By Hand - Shukur, Azurin; Hussein, Nur Izan Syahriah; Kamat, Seri Rahayu; Yuniawan, Dani (Penerbit Universiti Teknikal Malaysia Melaka, 2019)
This study was set to identify how working environment affected workers' stress level and to determine the differences of vibration absorbed by hand in both good and bad health conditions. To achieve the first aim, a survey method was employed to gather data from the workers who were involved in the composite cutting job. Meanwhile, to achieve the second aim, an experiment to investigate the effects of performing cutting job using hand tools was conducted on five participants with different health conditions. The results of the study revealed that the workers felt that their working environment was stressful. The workers who had bad health condition as average would absorb 237.8% (for 5mm thickness) and 17.46% (for 3mm thickness) more vibration from the hand tools while performing the cutting job than the others. The paper discusses whether workplace stress and vibration absorption from using hand tools will finally lead or contribute to health problems especially the hand arm vibration disease.